S71 Computer-Guided consultation in COPD practice. (14th November 2013) - Thompson, E B; Pearson, M G; Davies, L; McKnight, E; Trusdale, A; Sargeant, K; Angus, R M
Abstract : RATIONALE: We previously showed a comprehensive computer guided-consultation (containing prompts developed from NICE guidelines) in COPD primary care was feasible without specialist training, while preserving the autonomy of clinical decision making. The pilot study based on COPD primary care register, 88% had a proposed management change and 29% of patients had a diagnostic revision. We have re-examined the impact in real life to determine if this is repeated. Methods: We report on review of 2000 patients drawn from COPD registers across 78 practices. 459 (23%) did not have COPD based on spirometry. 1541 with COPD, had a mean (SD) age of 69.4 (9.8) yrs, 903 (58.6%)male, 1407 (91.6%) had been smokers and 597 (38.4%) were current smokers. The mean (SD) FEV1 was 1.48 (0.56) with a mean FEV1 percent predicted of 61.4 and a mean FEV1/FVC ratio of 52.4. The mean (SD) MRC score was 2.58 (0.9) and BMI was 27.0 (5.9). Results: Treatment modifications were implemented across various interventions. Pharmacological recommendations included the addition of: Short-acting bronchodilator in 75/1541 (4.9%), and a long-acting bronchodilator (LAMA) in 78/1541 (5.1%). Long-acting beta agonist/inhaled corticosteroid combination (LABA/ICS) was added in 75 patients including 37 with only moderate disease. In 32 (1.8%) patients the recommendation was to discontinue various inhaled medication and in 28 (1.6%) patients these were LABA/ICS combinations. In addition, 28.8% of patients currently smoking, accepted referral for smoking cessation support. 38 patients had hypoxia, 10 already on oxygen, and 4/28 (14.3%) referred for oxygen assessment. 33.3% of eligible patients were referred to pulmonary rehabilitation. 77.5% required and were provided with a written educational pack, and a formal crisis management plan formulated for 49.3% cases. Inhaler technique was inadequate in 10.2% of patients and in part drove the prescribing changes. Conclusion: Using computer guiding consultation in real life practice resulted in substantial management recommendations and diagnostic revisions. COPD care can be improved, using computer guided consultation which enables non specialists to achieve it.